Intrusion Detection on Software Defined Networking - Nagarjuna Reddy, Tella; Annapurani Panaiyappan, K (International Journal of Engineering and Technology, 2018)
Software Defined Networking and programmability on network have established themselves as current trends in IT by bringing autonomous operation with dynamic flow to network. Networks must be programmable, and it must be aware of the application in order to operate autonomously. Networks need to evolve to catch up with the current trends without losing their current status and operation, reliability, robustness, or security, and without distorting current investments. SDN is a transpiring network architecture where network control plane is distinguished from data plane and by that the network is directly programmable. This control, was initially bound in every network devices, enabled in the network to be abstracted for applications and services. Security is a major challenge for organizational and campus networks. The future of Internet depends on virtualization which is to provide numerous networks hosted the same physical hardware. This proposal takes a great advantage of the programmability provided by SDN to utilize Intrusion Detection System.